Differential effects of platelets and platelet inhibition by ticagrelor on TLR2- and TLR4-mediated inflammatory responses - Tunjungputri, Rahajeng N.; van der Ven, Andre J.; Riksen, Niels; Rongen, Gerard; Tacke, Sabine; van den Berg, T. N. A.; Fijnheer, Rob; Gomes, Marc E.; Dinarello, Charles A.; van de Veerdonk, Frank L.; Gasem, M. Hussein; Netea, Mihai G.; Joosten, Leo A. B.; de Groot, Philip G.; de Mast, Quirijn (Thrombosis and Haemostasis, 2015)
Platelets and platelet-monocyte interaction play an important role in inflammation. Both pro- and anti-inflammatory effects of platelet inhibition have been reported in animal models. This study aimed to investigate the effect of platelets and platelet inhibition by the new P2Y12 receptor antagonist ticagrelor on monocyte function, as assessed by cytokine responses to Toll-like Receptor (TLR) ligands. In a set of in vitro experiments, peripheral blood mononuclear cells (PBMC) incubated with the TLR2 ligand Pam3CSK4 produced less cytokines in the presence of platelets, whereas platelets increased the production of cytokines when PBMC were exposed to TLR4 ligand lipopolysaccharide (LPS). These effects of platelets were dependent on direct platelet-leukocyte aggregation and for the Pam3CSK4-induced response, on phagocytosis of platelets by monocytes. In a double blind, placebo-controlled crossover trial in healthy volunteers, a single oral dosage of 180 mg ticagrelor reduced platelet-monocyte complex (PMC) formation. This was associated with an increase in pro-inflammatory cytokines in blood exposed to Pam3CSK4, but a decrease in these cytokines in blood exposed to LPS. These findings show that platelets differentially modulate TLR2- and TLR4-mediated cytokine responses of PBMC. Through inhibition of platelet-leukocyte interaction, P2Y12 receptor antagonists may either exert a pro- or anti-inflammatory effect during infections depending on the TLR primarily involved.
Keywords: Platelets; ticagrelor; inflammation; Toll-like receptor; platelet-monocyte complex